Effect of Corporate Governance on the Financial Performance (Sustainability) of Microfinance Institutions in Ethiopia - Asmare, Ayenew Shibabaw; Kumar, Naveen (Gyan Management Journal, 2023)
This study investigated the relationship between the financialperformance and corporate governance of microfinance institutionsusing a sample of 25 MFIs from 2012 to 2021 with a balanced set ofpanel data. The study used secondary data and employed a descriptiveresearch design and a quantitative research approach. The empiricalresults showed that Female CEOs, Women directors, and internaauditors reporting directly to the board of directors and ProfitOrientation have a positive relationship and statistically significant effecton financial performance (ROA and OSS). The study recommendedas microfinance institutions should consider the gender diversity ofCEO and on the Board of directors and the board of directors also giveattention to internal auditors to report directly to them. Moreover, thestudy suggested for future researchers may be interested in validatingthe stability of the result and providing additional results for this studyby including other variables (Internal and external).
Keywords: Microfinance; financial performance; Governance; internal and external factors